IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN ETIKA SISWA SDIT ALAM NURUL ISLAM DUA NGAWI - Darmanto (LPPM STAI Muhammadiyah Probolinggo, 2025)
The purpose of this study is to understand how Islamic education is implemented at SDIT Alam Nurul Islam Dua Ngawi with the aim of enhancing student ethics. This study is a kualitatif study using a kasus study approach. Data collection is done by documentation, observation, and wawancara. Sumber and the triangulation method are used to ensure the accuracy of the data. The study's findings indicate that the implementation of Islamic education at SDIT Alam Nurul Islam Dua Ngawi promotes the integration of ethical principles into all educational activities, school-related activities (such as 5S, Sholat berjamaah, and tadabur alam), and school-related community activities.